Abstracts of the 25th Biennial International Congress on Thrombosis - Vittorio Pengo; Paolo Prandoni (Proceedings, 2018)
This Issue collates the abstracts presented at the 25th Biennial International Congress on Thrombosis held on 23–26 May 2018. Prevention and treatment of thromboembolic events is a main issue in medicine that involves all the components of the health care system. Recently, a strong boost in this field came from the introduction of new antithrombotic agents whose use is expanding with the need for more information obtained by real-life studies. Thus, ICT 2018 was an important venue to compare clinical experiences and learn new advances in basic and pharmacological sciences.